1998
DOI: 10.1017/s0959259898008089
|View full text |Cite
|
Sign up to set email alerts
|

A review of instrumental ADL assessments for use with elderly people

Abstract: The concept of formal or standardized tests for assessing function came to the fore in the 1960s. Katz et al. acknowledged the hierarchical nature of activities of daily living (ADL) such as eating, continence, transferring, going to the toilet, dressing and bathing in his ’Index of ADL’ and by 1968 ‘ADL’ was an accepted Index Medicus category. The definition of instrumental activities of daily living (IADL) began in 1969 with the work of Lawton and Brody who presented two scales to assess function which recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 0 publications
2
35
0
4
Order By: Relevance
“…Ward et al [35] observed that no IADL scale is right for every person and there is no consensus about which activities should be included. More updated reviews also conclude that there is no ‘gold standard' on how to assess IADL [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ward et al [35] observed that no IADL scale is right for every person and there is no consensus about which activities should be included. More updated reviews also conclude that there is no ‘gold standard' on how to assess IADL [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring functional ability is an important task in research and clinical settings, especially for elderly patients (Katz, 1983;Myers, 1992;Ward, Jagger, & Harper, 1998). A number of measures of instrumental activities of daily living (IADL; e.g., using the telephone, managing personal finances, preparing food) have been developed for this purpose (Lindeboom, Vermeulen, Holman, & De Haan, 2003;Ward et al, 1998), and Lawton and Brody's (1969) eight-item IADL scale is among the most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…A number of measures of instrumental activities of daily living (IADL; e.g., using the telephone, managing personal finances, preparing food) have been developed for this purpose (Lindeboom, Vermeulen, Holman, & De Haan, 2003;Ward et al, 1998), and Lawton and Brody's (1969) eight-item IADL scale is among the most commonly used. Although Lawton and Brody initially scored this instrument using a hierarchical Guttman framework, sums of dichotomously (less able versus more able), trichotomously (0, 1, 2) and polytomously (e.g., 1-5 point scale of increasing disability) keyed items are common, and some researchers advocate Rasch (empirically equal-interval) scores for IADL scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IADLs are not necessary for fundamental functioning, but permit an individual to live independently in a community. Since IADL function is often lost before ADL function, assessment of IADLs may identify incipient cognitive or physical decline in an otherwise capable and healthy older adult (Ward, Jagger, & Harper, 1998). A combined summary score ranges from 0 to 8 (low function to high function) on the Lawton Scale.…”
Section: Activities Of Daily Living (Adl) Index and The Lawton Instrumentioning
confidence: 99%